Jumping exercise combined with collagen supplementation preserves bone mineral density in elite cyclists - Hilkens, L.; van Schijndel, N.; Weijer, V. C.; Decroix, L.; Bons, J.; van Loon, L. J.; van Dijk, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
This study assessed the effect of combined jump training and collagen supplementation on bone mineral density (BMD) in elite road-race cyclists. In this open-label, randomized study with two parallel groups, 36 young (21 ± 3 years) male (n = 8) and female (n = 28) elite road-race cyclists were allocated to either an intervention (INT: n = 18) or a no-treatment control (CON: n = 18) group. The 18-week intervention period, conducted during the off-season, comprised five 5-min bouts of jumping exercise per week, with each bout preceded by the ingestion of 15 g hydrolyzed collagen. Before and after the intervention, BMD of various skeletal sites and trabecular bone score of the lumbar spine were assessed by dual-energy X-ray absorptiometry, along with serum bone turnover markers procollagen Type I N propeptide and carboxy-terminal cross-linking telopeptide of Type I collagen. BMD of the femoral neck decreased in CON (from 0.789 ± 0.104 to 0.774 ± 0.095 g/cm2), while being preserved in INT (from 0.803 ± 0.058 to 0.809 ± 0.066 g/cm2; Time × Treatment, p < .01). No differences between treatments were observed for changes in BMD at the total hip, lumbar spine, and whole body (Time × Treatment, p > .05 for all). Trabecular bone score increased from 1.38 ± 0.08 to 1.40 ± 0.09 in CON and from 1.46 ± 0.08 to 1.47 ± 0.08 in INT, respectively (time effect: p < .01), with no differences between treatments (Time × Treatment: p = .33). Serum procollagen Type I N propeptide concentrations decreased to a similar extent in CON (83.6 ± 24.8 to 71.4 ± 23.1 ng/ml) and INT (82.8 ± 30.7 to 66.3 ± 30.6; time effect, p < .001; Time × Treatment, p = .22). Serum carboxy-terminal cross-linking telopeptide of Type I collagen concentrations did not change over time, with no differences between treatments (time effect, p = .08; Time × Treatment, p = .58). In conclusion, frequent short bouts of jumping exercise combined with collagen supplementation beneficially affects femoral neck BMD in elite road-race cyclists.